2022
DOI: 10.1111/jdv.18473
|View full text |Cite
|
Sign up to set email alerts
|

Methylated miRNAsmay serve as potential biomarkers and therapeutic targets for hidradenitis suppurativa

Abstract: Background Hidradenitis suppurativa (HS) is a chronic inflammatory disease influenced by genetics, non‐genetic and environmental factors that modulate miRNA expression. Currently, no miRNA data are available for HS. In this study, we profiled DNA methylation patterns of miRNA genes associated with HS susceptibility. Objectives Identify miRNA gene methylation profiles associated with HS susceptibility. This study examined the methylation patterns of DNAs from 24 healthy controls and 24 patients with HS using Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 167 publications
0
21
0
Order By: Relevance
“…Ideally, studies should include the water type orally consumed in the exposome to modify the cutaneous outcomes, especially in complex skin disorders, in which susceptible genes [ 29 , 30 ] interact with exposure to manifest the pathological phenotype (i.e., psoriasis or hidradenitis suppurativa) [ 31 , 32 ]. In fact, exposures may condition the epigenetics that modulate genes expression [ 33 ] and even drug response [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, studies should include the water type orally consumed in the exposome to modify the cutaneous outcomes, especially in complex skin disorders, in which susceptible genes [ 29 , 30 ] interact with exposure to manifest the pathological phenotype (i.e., psoriasis or hidradenitis suppurativa) [ 31 , 32 ]. In fact, exposures may condition the epigenetics that modulate genes expression [ 33 ] and even drug response [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the methodology has been previously described. 8 Illumina Infinium methylation EPIC BeadChip Genome-wide DNA methylation analysis was performed on 500 ng of bisulphite-treated genomic DNA using the Illumina The Infinium HumanMethylation450 BeadChip (Illumina Inc., San Diego, CA) according to the manufacturer's protocol 30 at the Beaumont Health Genomics (core facility). All cases and controls, as well as age and gender, were randomly distributed on arrays for successful microarray experiments.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…On the other hand, when NZ10 mice were predisposed with obesity, Type 2 diabetes and hepatic steatosis; fed with high protein fish oil diet and examined for the biochemical and physical functions, results showed that the diet prevented steatosis and reduced serum cholesterol and triglycerides, and the diet repressed the hepatic expression of fatty acid metabolic regulators like peroxisome proliferator activated receptor gamma co-activator-1, fatty acid synthase, fatty acid binding protein-4 and apolipoprotein A4 genes in these mice [ 18 ]. To prove miR-205 has the potential to act as a biomarker for other diseases such as Hidradenitis suppurativa, it was found that this, along with other RNAs, could be important for regulating skin and wound repair and age-related alterations [ 21 ].…”
Section: Role Of Mir-205 In Liver Diseasesmentioning
confidence: 99%